In mathematical analysis , the Minkowski inequality establishes that the Lp spaces are normed vector spaces . Let
S
{\textstyle S}
be a measure space , let
1
≤
p
<
∞
{\textstyle 1\leq p<\infty }
and let
f
{\textstyle f}
and
g
{\textstyle g}
be elements of
L
p
(
S
)
.
{\textstyle L^{p}(S).}
Then
f
+
g
{\textstyle f+g}
is in
L
p
(
S
)
,
{\textstyle L^{p}(S),}
and we have the triangle inequality
‖
f
+
g
‖
p
≤
‖
f
‖
p
+
‖
g
‖
p
{\displaystyle \|f+g\|_{p}\leq \|f\|_{p}+\|g\|_{p}}
with equality for
1
<
p
<
∞
{\textstyle 1<p<\infty }
if and only if
f
{\textstyle f}
and
g
{\textstyle g}
are positively linearly dependent ; that is,
f
=
λ
g
{\textstyle f=\lambda g}
for some
λ
≥
0
{\textstyle \lambda \geq 0}
or
g
=
0.
{\textstyle g=0.}
Here, the norm is given by:
‖
f
‖
p
=
(
∫
|
f
|
p
d
μ
)
1
p
{\displaystyle \|f\|_{p}=\left(\int |f|^{p}d\mu \right)^{\frac {1}{p}}}
if
p
<
∞
,
{\textstyle p<\infty ,}
or in the case
p
=
∞
{\textstyle p=\infty }
by the essential supremum
‖
f
‖
∞
=
e
s
s
s
u
p
x
∈
S
|
f
(
x
)
|
.
{\displaystyle \|f\|_{\infty }=\operatorname {ess\ sup} _{x\in S}|f(x)|.}
The Minkowski inequality is the triangle inequality in
L
p
(
S
)
.
{\textstyle L^{p}(S).}
In fact, it is a special case of the more general fact
‖
f
‖
p
=
sup
‖
g
‖
q
=
1
∫
|
f
g
|
d
μ
,
1
p
+
1
q
=
1
{\displaystyle \|f\|_{p}=\sup _{\|g\|_{q}=1}\int |fg|d\mu ,\qquad {\tfrac {1}{p}}+{\tfrac {1}{q}}=1}
where it is easy to see that the right-hand side satisfies the triangular inequality.
Like Hölder's inequality , the Minkowski inequality can be specialized to sequences and vectors by using the counting measure :
(
∑
k
=
1
n
|
x
k
+
y
k
|
p
)
1
/
p
≤
(
∑
k
=
1
n
|
x
k
|
p
)
1
/
p
+
(
∑
k
=
1
n
|
y
k
|
p
)
1
/
p
{\displaystyle {\biggl (}\sum _{k=1}^{n}|x_{k}+y_{k}|^{p}{\biggr )}^{1/p}\leq {\biggl (}\sum _{k=1}^{n}|x_{k}|^{p}{\biggr )}^{1/p}+{\biggl (}\sum _{k=1}^{n}|y_{k}|^{p}{\biggr )}^{1/p}}
for all real (or complex ) numbers
x
1
,
…
,
x
n
,
y
1
,
…
,
y
n
{\textstyle x_{1},\dots ,x_{n},y_{1},\dots ,y_{n}}
and where
n
{\textstyle n}
is the cardinality of
S
{\textstyle S}
(the number of elements in
S
{\textstyle S}
).
In probabilistic terms, given the probability space
(
Ω
,
F
,
P
)
,
{\displaystyle (\Omega ,{\mathcal {F}},\mathbb {P} ),}
and
E
{\displaystyle \mathbb {E} }
denote the expectation operator for every real- or complex-valued random variables
X
{\displaystyle X}
and
Y
{\displaystyle Y}
on
Ω
,
{\displaystyle \Omega ,}
Minkowski's inequality reads
(
E
[
|
X
+
Y
|
p
)
1
p
⩽
(
E
[
|
X
|
p
]
)
1
p
+
(
E
[
|
Y
|
p
]
)
1
p
.
{\displaystyle \left(\mathbb {E} [|X+Y|^{p}\right)^{\frac {1}{p}}\leqslant \left(\mathbb {E} [|X|^{p}]\right)^{\frac {1}{p}}+\left(\mathbb {E} [|Y|^{p}]\right)^{\frac {1}{p}}.}
The inequality is named after the German mathematician Hermann Minkowski .
Proof by Hölder's inequality
edit
First, we prove that
f
+
g
{\textstyle f+g}
has finite
p
{\textstyle p}
-norm if
f
{\textstyle f}
and
g
{\textstyle g}
both do, which follows by
|
f
+
g
|
p
≤
2
p
−
1
(
|
f
|
p
+
|
g
|
p
)
.
{\displaystyle |f+g|^{p}\leq 2^{p-1}(|f|^{p}+|g|^{p}).}
Indeed, here we use the fact that
h
(
x
)
=
|
x
|
p
{\textstyle h(x)=|x|^{p}}
is convex over
R
+
{\textstyle \mathbb {R} ^{+}}
(for
p
>
1
{\textstyle p>1}
) and so, by the definition of convexity,
|
1
2
f
+
1
2
g
|
p
≤
|
1
2
|
f
|
+
1
2
|
g
|
|
p
≤
1
2
|
f
|
p
+
1
2
|
g
|
p
.
{\displaystyle \left|{\tfrac {1}{2}}f+{\tfrac {1}{2}}g\right|^{p}\leq \left|{\tfrac {1}{2}}|f|+{\tfrac {1}{2}}|g|\right|^{p}\leq {\tfrac {1}{2}}|f|^{p}+{\tfrac {1}{2}}|g|^{p}.}
This means that
|
f
+
g
|
p
≤
1
2
|
2
f
|
p
+
1
2
|
2
g
|
p
=
2
p
−
1
|
f
|
p
+
2
p
−
1
|
g
|
p
.
{\displaystyle |f+g|^{p}\leq {\tfrac {1}{2}}|2f|^{p}+{\tfrac {1}{2}}|2g|^{p}=2^{p-1}|f|^{p}+2^{p-1}|g|^{p}.}
Now, we can legitimately talk about
‖
f
+
g
‖
p
.
{\textstyle \|f+g\|_{p}.}
If it is zero, then Minkowski's inequality holds. We now assume that
‖
f
+
g
‖
p
{\textstyle \|f+g\|_{p}}
is not zero. Using the triangle inequality and then Hölder's inequality , we find that
‖
f
+
g
‖
p
p
=
∫
|
f
+
g
|
p
d
μ
=
∫
|
f
+
g
|
⋅
|
f
+
g
|
p
−
1
d
μ
≤
∫
(
|
f
|
+
|
g
|
)
|
f
+
g
|
p
−
1
d
μ
=
∫
|
f
|
|
f
+
g
|
p
−
1
d
μ
+
∫
|
g
|
|
f
+
g
|
p
−
1
d
μ
≤
(
(
∫
|
f
|
p
d
μ
)
1
p
+
(
∫
|
g
|
p
d
μ
)
1
p
)
(
∫
|
f
+
g
|
(
p
−
1
)
(
p
p
−
1
)
d
μ
)
1
−
1
p
Hölder's inequality
=
(
‖
f
‖
p
+
‖
g
‖
p
)
‖
f
+
g
‖
p
p
‖
f
+
g
‖
p
{\displaystyle {\begin{aligned}\|f+g\|_{p}^{p}&=\int |f+g|^{p}\,\mathrm {d} \mu \\&=\int |f+g|\cdot |f+g|^{p-1}\,\mathrm {d} \mu \\&\leq \int (|f|+|g|)|f+g|^{p-1}\,\mathrm {d} \mu \\&=\int |f||f+g|^{p-1}\,\mathrm {d} \mu +\int |g||f+g|^{p-1}\,\mathrm {d} \mu \\&\leq \left(\left(\int |f|^{p}\,\mathrm {d} \mu \right)^{\frac {1}{p}}+\left(\int |g|^{p}\,\mathrm {d} \mu \right)^{\frac {1}{p}}\right)\left(\int |f+g|^{(p-1)\left({\frac {p}{p-1}}\right)}\,\mathrm {d} \mu \right)^{1-{\frac {1}{p}}}&&{\text{ Hölder's inequality}}\\&=\left(\|f\|_{p}+\|g\|_{p}\right){\frac {\|f+g\|_{p}^{p}}{\|f+g\|_{p}}}\end{aligned}}}
We obtain Minkowski's inequality by multiplying both sides by
‖
f
+
g
‖
p
‖
f
+
g
‖
p
p
.
{\displaystyle {\frac {\|f+g\|_{p}}{\|f+g\|_{p}^{p}}}.}
Proof by a direct convexity argument
edit
Given
t
∈
(
0
,
1
)
{\displaystyle t\in (0,1)}
, one has, by convexity,
|
f
+
g
|
p
=
|
(
1
−
t
)
f
1
−
t
+
t
g
t
|
p
≤
(
1
−
t
)
|
f
1
−
t
|
p
+
t
|
g
t
|
p
=
|
f
|
p
(
1
−
t
)
p
−
1
+
|
g
|
p
t
p
−
1
.
{\displaystyle |f+g|^{p}={\Bigl |}(1-t){\frac {f}{1-t}}+t{\frac {g}{t}}{\Bigr |}^{p}\leq (1-t){\Bigl |}{\frac {f}{1-t}}{\Bigr |}^{p}+t{\Bigl |}{\frac {g}{t}}{\Bigr |}^{p}={\frac {|f|^{p}}{(1-t)^{p-1}}}+{\frac {|g|^{p}}{t^{p-1}}}.}
By integration this leads to
∫
S
|
f
+
g
|
p
d
μ
≤
1
(
1
−
t
)
p
−
1
∫
S
|
f
|
p
d
μ
+
1
t
p
−
1
∫
S
|
g
|
p
d
μ
.
{\displaystyle \int _{S}|f+g|^{p}\,\mathrm {d} \mu \leq {\frac {1}{(1-t)^{p-1}}}\int _{S}|f|^{p}\,\mathrm {d} \mu +{\frac {1}{t^{p-1}}}\int _{S}|g|^{p}\,\mathrm {d} \mu .}
One takes then
t
=
‖
g
‖
p
‖
f
‖
p
+
‖
g
‖
p
{\displaystyle t={\frac {\Vert g\Vert _{p}}{\Vert f\Vert _{p}+\Vert g\Vert _{p}}}}
to reach the conclusion.
Minkowski's integral inequality
edit
Suppose that
(
S
1
,
μ
1
)
{\textstyle (S_{1},\mu _{1})}
and
(
S
2
,
μ
2
)
{\textstyle (S_{2},\mu _{2})}
are two 𝜎-finite measure spaces and
F
:
S
1
×
S
2
→
R
{\textstyle F:S_{1}\times S_{2}\to \mathbb {R} }
is measurable. Then Minkowski's integral inequality is:
[
∫
S
2
|
∫
S
1
F
(
x
,
y
)
μ
1
(
d
x
)
|
p
μ
2
(
d
y
)
]
1
p
≤
∫
S
1
(
∫
S
2
|
F
(
x
,
y
)
|
p
μ
2
(
d
y
)
)
1
p
μ
1
(
d
x
)
,
p
∈
[
1
,
∞
)
{\displaystyle \left[\int _{S_{2}}\left|\int _{S_{1}}F(x,y)\,\mu _{1}(\mathrm {d} x)\right|^{p}\mu _{2}(\mathrm {d} y)\right]^{\frac {1}{p}}~\leq ~\int _{S_{1}}\left(\int _{S_{2}}|F(x,y)|^{p}\,\mu _{2}(\mathrm {d} y)\right)^{\frac {1}{p}}\mu _{1}(\mathrm {d} x),\quad p\in [1,\infty )}
with obvious modifications in the case
p
=
∞
.
{\textstyle p=\infty .}
If
p
>
1
,
{\textstyle p>1,}
and both sides are finite, then equality holds only if
|
F
(
x
,
y
)
|
=
φ
(
x
)
ψ
(
y
)
{\textstyle |F(x,y)|=\varphi (x)\,\psi (y)}
a.e. for some non-negative measurable functions
φ
{\textstyle \varphi }
and
ψ
.
{\textstyle \psi .}
If
μ
1
{\textstyle \mu _{1}}
is the counting measure on a two-point set
S
1
=
{
1
,
2
}
,
{\textstyle S_{1}=\{1,2\},}
then Minkowski's integral inequality gives the usual Minkowski inequality as a special case: for putting
f
i
(
y
)
=
F
(
i
,
y
)
{\textstyle f_{i}(y)=F(i,y)}
for
i
=
1
,
2
,
{\textstyle i=1,2,}
the integral inequality gives
‖
f
1
+
f
2
‖
p
=
(
∫
S
2
|
∫
S
1
F
(
x
,
y
)
μ
1
(
d
x
)
|
p
μ
2
(
d
y
)
)
1
p
≤
∫
S
1
(
∫
S
2
|
F
(
x
,
y
)
|
p
μ
2
(
d
y
)
)
1
p
μ
1
(
d
x
)
=
‖
f
1
‖
p
+
‖
f
2
‖
p
.
{\displaystyle \|f_{1}+f_{2}\|_{p}=\left(\int _{S_{2}}\left|\int _{S_{1}}F(x,y)\,\mu _{1}(\mathrm {d} x)\right|^{p}\mu _{2}(\mathrm {d} y)\right)^{\frac {1}{p}}\leq \int _{S_{1}}\left(\int _{S_{2}}|F(x,y)|^{p}\,\mu _{2}(\mathrm {d} y)\right)^{\frac {1}{p}}\mu _{1}(\mathrm {d} x)=\|f_{1}\|_{p}+\|f_{2}\|_{p}.}
If the measurable function
F
:
S
1
×
S
2
→
R
{\textstyle F:S_{1}\times S_{2}\to \mathbb {R} }
is non-negative then for all
1
≤
p
≤
q
≤
∞
,
{\textstyle 1\leq p\leq q\leq \infty ,}
‖
‖
F
(
⋅
,
s
2
)
‖
L
p
(
S
1
,
μ
1
)
‖
L
q
(
S
2
,
μ
2
)
≤
‖
‖
F
(
s
1
,
⋅
)
‖
L
q
(
S
2
,
μ
2
)
‖
L
p
(
S
1
,
μ
1
)
.
{\displaystyle \left\|\left\|F(\,\cdot ,s_{2})\right\|_{L^{p}(S_{1},\mu _{1})}\right\|_{L^{q}(S_{2},\mu _{2})}~\leq ~\left\|\left\|F(s_{1},\cdot )\right\|_{L^{q}(S_{2},\mu _{2})}\right\|_{L^{p}(S_{1},\mu _{1})}\ .}
This notation has been generalized to
‖
f
‖
p
,
q
=
(
∫
R
m
[
∫
R
n
|
f
(
x
,
y
)
|
q
d
y
]
p
q
d
x
)
1
p
{\displaystyle \|f\|_{p,q}=\left(\int _{\mathbb {R} ^{m}}\left[\int _{\mathbb {R} ^{n}}|f(x,y)|^{q}\mathrm {d} y\right]^{\frac {p}{q}}\mathrm {d} x\right)^{\frac {1}{p}}}
for
f
:
R
m
+
n
→
E
,
{\textstyle f:\mathbb {R} ^{m+n}\to E,}
with
L
p
,
q
(
R
m
+
n
,
E
)
=
{
f
∈
E
R
m
+
n
:
‖
f
‖
p
,
q
<
∞
}
.
{\textstyle {\mathcal {L}}_{p,q}(\mathbb {R} ^{m+n},E)=\{f\in E^{\mathbb {R} ^{m+n}}:\|f\|_{p,q}<\infty \}.}
Using this notation, manipulation of the exponents reveals that, if
p
<
q
,
{\textstyle p<q,}
then
‖
f
‖
q
,
p
≤
‖
f
‖
p
,
q
.
{\textstyle \|f\|_{q,p}\leq \|f\|_{p,q}.}
Generalizations to other functions
edit
^ Mulholland, H. P. (1949). "On Generalizations of Minkowski's Inequality in the Form of a Triangle Inequality". Proceedings of the London Mathematical Society . s2-51 (1): 294– 307. doi :10.1112/plms/s2-51.4.294 .
Bahouri, Hajer ; Chemin, Jean-Yves ; Danchin, Raphaël (2011). Fourier Analysis and Nonlinear Partial Differential Equations . Grundlehren der mathematischen Wissenschaften. Vol. 343. Berlin, Heidelberg: Springer. ISBN 978-3-642-16830-7 . OCLC 704397128 .
Hardy, G. H. ; Littlewood, J. E. ; Pólya, G. (1988). Inequalities . Cambridge Mathematical Library (second ed.). Cambridge: Cambridge University Press. ISBN 0-521-35880-9 .
Minkowski, H. (1953). Geometrie der Zahlen . Chelsea. .
Stein, Elias (1970). Singular integrals and differentiability properties of functions . Princeton University Press. .
M.I. Voitsekhovskii (2001) [1994], "Minkowski inequality" , Encyclopedia of Mathematics , EMS Press
Lohwater, Arthur J. (1982). "Introduction to Inequalities" .